Dominance of Mating Type A1 and Indication of Epigenetic Effects During Early Stages of Mating in Phytophthora infestans - Tzelepis, Georgios; Hodén, Kristian Persson; Fogelqvist, Johan; Åsman, Anna K. M.; Vetukuri, Ramesh R.; Dixelius, Christina (Frontiers in Microbiology, 2020)
The potato late blight pathogen Phytophthora infestans has both an asexual and a sexual mode of reproduction. In Scandinavia, the pathogen is reproducing sexually on a regular basis, whereas clonal lineages dominate in other geographical regions. This study aimed at elucidating events or key genes underlying this difference in sexual behavior. First, the transcriptomes of eight strains, known as either clonal or sexual, were compared during early stages of mating. Principal component analysis (PCA) divided the samples in two clusters A and B and a clear grouping of the mating samples together with the A1 mating type parents was observed. Induction of genes encoding DNA adenine N6-methylation (6mA) methyltransferases clearly showed a bias towards the cluster A. In contrast, the Avrblb2 effector gene family was highly induced in most of the mating samples and was associated with cluster B in the PCA, similarly to genes coding for acetyl-transferases, which play an important role in RXLR modification prior to secretion. Avrblb2 knock-down strains displayed a reduction in virulence and oospore formation, suggesting a role during the mating process. In conclusion, a number of gene candidates important for the reproductive processes were revealed. The results suggest a possible epigenetic influence and involvement of specific RXLR effectors in mating-related processes.